Maze learning and memory in a decapod crustacean - Mary Gagen (Biology Letters, 2019)
Spatial learning is an ecologically important trait well studied in vertebrates but only in a few invertebrates and poorly understood in crustaceans. We explored the ability of European shore crabs, Carcinus maenas, to learn a complex maze over four consecutive weeks using food as a motivator. Crabs showed a steady improvement in their ability to learn and use the maze to find food during this conditioning period. Improvements were seen both in the time taken to find the food and in a reduciton in the number of wrong turns taken before the food was located. Crabs also clearly showed the ability to remember the maze. When we returned them to the maze following a two week break, but without any food in the maze, they all returned to the end of the maze in under eight minutes. Crabs that had not been conditioned to the maze took far longer to reach the end and 42% of individuals did not get to the end of the maze at all during a one-hour study period. Our study provides an initial description of spatial learning in the European shore crab. Bettering our understanding of this adaptive trait will develop our understanding of resource exploitation by benthic crustaceans and their ecological roles.